Front Cover: Asymmetric Construction of All‐Carbon Quaternary Stereocenters via Organocatalytic α‐Hydroxymethylation of Malonic Diesters Using Aqueous Formaldehyde (Asian J. Org. Chem. 8/2022). Issue 8 (3rd August 2022) - Kanemitsu, Takuya; Ozasa, Eisuke; Murase, Yuria; Sakaue, Susumu; Miyazaki, Michiko; Nagata, Kazuhiro; Itoh, Takashi
Abstract : Formaldehyde is a potent one‐carbon electrophile for organic synthesis. However, there are few synthetic approaches using aqueous formaldehyde (formalin). This paper describes an organocatalyzed enantioselective α‐hydroxymethylation of malonic diesters with aqueous formaldehyde. Formaldehyde would react catalytically by transferring from the aqueous phase to the organic phase, providing chiral versatile malonic diester derivatives which contain a quaternary stereogenic center. More information can be found in the Research Article by Takuya Kanemitsu et al .